Comparative compression ignition engine performance, combustion, and emission characteristics, and trace metals in particulates from Waste cooking oil, Jatropha and Karanja oil derived biodiesels. (15th January 2019) - Patel, Chetankumar; Chandra, Krishn; Hwang, Joonsik; Agarwal, Rashmi A.; Gupta, Neeraj; Bae, Choongsik; Gupta, Tarun; Agarwal, Avinash Kumar
Graphical abstract: Highlights: Biodiesels exhibited higher P, HRRmax but shorter CD. Biodiesels showed higher smoke opacity due to higher viscosity. Lower HC, NOx and trace metals in particulates from biodiesels. Trace metals in particulates reduced with increasing engine load. Most trace metal concentrations in biodiesel particulates were lower. Abstract: In the present study, comparison of performance, combustion and emission characteristics of a single cylinder compression ignition (CI) genset engine fueled by biodiesels derived from Waste cooking oil (WCO), Jatropha and Karanja oils vis-á-vis baseline mineral diesel has been carried out. Performance and combustion investigations were carried out at constant engine speed (1500 rpm) and six engine loads (0–100%). WCO biodiesel showed slightly higher heat release rate (HRR) than baseline mineral diesel, while it was slightly lower for Karanja and Jatropha biodiesels. Hydrocarbons (HC) and oxides of nitrogen (NOX ) emissions were lower, while carbon monoxide (CO) emission was relatively higher for biodiesels compared to baseline diesel. Smoke opacity was higher for Karanja and Jatropha biodiesels compared to baseline diesel. WCO biodiesel exhibited comparable smoke opacity with baseline mineral diesel except at full load, where it was relatively lower. Particulates were collected from the engine exhaust on a quartz filter paper using a partial flow dilution tunnel at 50 and 100% engine loads, for trace metal analysis using inductively coupled plasma optical emission spectroscopy (ICP-OES). It was found that trace metals such as Ca, Cu, Fe, K, Mg, Na, Zn and Al showed higher concentrations in particulates from all test fuels, while Ba, Cd, Cr, Mn and Mo showed relatively lower concentrations in the particulates collected.